What Factors Affecting Patient Satisfaction? - Eliza, Yulina; Apriyeni, Deltri; Sutiyem, Sutiyem; Trismiyanti, Dessy (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Raising patient happiness is one of the objectives for raising the bar for healthcare services. It has been demonstrated that people who are happy with the medical care they receive are more likely to heed advice, stay faithful, or stick to treatment regimens. The goal of research at RSUD Kota Padang is to ascertain how competency, interpersonal communication, and service quality affect the happiness of BPJS patients. Associative and descriptive thinking were combined in the quantitative methods employed for this investigation. A purposive sampling procedure yielded a sample size of 100 individuals, and SPSS was utilized as an analysis tool to do multiple linear regression. The results of research indicate that: (1) Patient satisfaction is impacted by competence. (2) Interpersonal communication has a major impact on patient satisfaction. (3) The standard of care greatly affects patient satisfaction.